Pemanfaatan Model Tempat Sampah Bervideo Terhadap Ketepatan Memilah Smapah Siswa Sekolah Dasar Negeri di Desa Banyuraden, Gamping, Sleman - Imam Setya Arifian; Mohammad Mirza Fauzie; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Waste management in schools becomes one of the efforts in the forming of comfortable andclean schools. Waste bin with video is made to stimulate students to be able to properly dispose the waste according to their types with the help of audiovisual stimulation. The purpose ofthis research was to know the usefulnes of waste bin with video model toward the accuracy ofstudents in sorting the waste in accordance with the instructions. The research was an experiment with post test only control group design and was taken place in two elementary schools,i.e. Kanoman Public Elementary School as the control group and Patran Public ElementarySchool as the treatment group, both school are located in Banyuraden Village of Gamping, Sleman Regency, and as the respondents were all students of grade four. The study results showthat the percentage of sorting in the treatment group are 79,41 % for paper waste, 87,50 % forplastic waste, and 86,66 % for food waste; meanwhile in the control group, the percentages are68,96 % for paper waste, 70,37 % for plastic waste and 68,18 % for food waste. The dataanalysis by using independent t-test at ? = 0,05, yielded p-values of 0,022 which can be concluded that the waste bins with video do influence the accuracy of elementary school studentsin waste types sorting in mutual accordance with the given instructions.